Comparison of Pulse Rate and Blood Pressure between Obese and Non-Obese Young Adults (Bangladesh Medical Journal, 2023)
Obesity has been reported to be associated with a number of cardiovascular diseases. Some researchers forecast that obesity may contribute to increase prevalence of high blood pressure in young adults. To compare pulse rate and blood pressure between young obese and non-obese subjects, this cross-sectional analytical study was done in the Department of Physiology, Sylhet MAG Osmani Medical College from January to December 2017. Fifty obese (BMI ≥27.5 kg/m2) and age-sex matched non-obese (BMI 18.5-22.9 kg/m2) young adult were selected. The age (35.56 ± 3.02 years versus 32.40 ± 4.20 years; p=0.116) and sex 26 (52.0%) male versus 31 (62.0%) male; p=0.313) were not differ between obese and non-obese subjects. The mean resting pulse rate (82.98 ± 3.50 beats /minute versus 72.64 ± 3.58 beats/minute; p